Investigation of Performance of Stone Fin Solar Still Absorber by Water Depth Variations - Ismail*, Nova Risdiyanto; Hermawan, Dadang; Suwandono, Purbo; Wicaksono, Leo Hutri (Aceh International Journal of Science and Technology, 2023)
Passive Solar is still suitable for Indonesia's islands and coastal areas. Various attempts have been made to increase the performance of passive solar stills, including using porous materials, fins absorber models, and making water in the form of a thin layer. This study aims to increase the distillate output and Efficiency of Solar still. This study's method compares stone fin solar stills absorbers using water depth variations of 1 cm, 2 cm, and 3 cm with conventional solar stills at a water depth of 1 cm. The study resulted in the distillate output of stone fin solar still absorber of 3.35 (liter/m2 .day) higher than the conventional solar stills 2.44 (liter/m2 .day) at a depth of 1 cm. The highest Efficiency of solar stills using the stone fin solar still absorbers is 58.45% higher than conventional solar stills, 43.60% at a depth of 1 cm. Solar stills with lower water depths resulted in higher distillate output and Efficiency. Solar stills using stone fin absorbent plates produce higher productivity and Efficiency than conventional ones.